2022
DOI: 10.1097/cm9.0000000000002158
|View full text |Cite
|
Sign up to set email alerts
|

Functional mutations of SARS-CoV-2: implications to viral transmission, pathogenicity and immune escape

Abstract: The pandemic of coronavirus disease 2019 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to major public health challenges globally. The increasing viral lineages identified indicate that the SARS-CoV-2 genome is evolving at a rapid rate. Viral genomic mutations may cause antigenic drift or shift, which are important ways by which SARS-CoV-2 escapes the human immune system and changes its transmissibility and virulence. Herein, we summarize the functional mutations in SARS-CoV-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 152 publications
0
5
0
Order By: Relevance
“…The study by Oulas et al demonstrates that the P13L mutation can influence both transmissibility and death rates. Specifically, this mutation is associated with a decrease in the number of deaths and cases per million 15 , 25 . For the P13L mutation, our experiments showed that it leads to structural stabilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Oulas et al demonstrates that the P13L mutation can influence both transmissibility and death rates. Specifically, this mutation is associated with a decrease in the number of deaths and cases per million 15 , 25 . For the P13L mutation, our experiments showed that it leads to structural stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account that viral proteins do not mutate singularly, and the impact on pathogenesis is likely influenced by the combination of multiple mutations in different proteins, it becomes a complicated task. Therefore, determining the relationship between mutations and disease outcomes requires a comprehensive analysis of various mutation combinations rather than focusing on individual mutations in isolation 12 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The impact of COVID-19 on individuals with diabetes appears to vary across different waves of the pandemic. This variation likely stems from changes in the virulence and pathogenicity of SARS-CoV-2 variants over time, as well as fluctuations in healthcare resources and accessibility [11].…”
Section: Discussionmentioning
confidence: 99%
“…These mutations in the viral genome, have impacted various aspects of the pandemic response [1,2]. Notably, mutations in the spike gene and other accessory genes have been identified, affecting transmission dynamics, vaccine efficacy, disease severity, therapeutic interventions, diagnostic testing, and public health measures [3,4]. Within the spike gene, several mutations such as R203K, G204R, N501Y, E484K, L452R, and E484Q have been identified, which have the potential to increase viral replication, fitness, and immune evasion [3,4].…”
Section: Introductionmentioning
confidence: 99%